2010
DOI: 10.1007/s00425-010-1126-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a calmodulin involved in the signal transduction chain of gravitaxis in Euglena gracilis

Abstract: The unicellular flagellate Euglena gracilis shows a negative gravitactic behavior. This is based on physiological mechanisms which in the past have been indirectly assessed. Meanwhile, it was possible to isolate genes involved in the signal transduction chain of gravitaxis. The DNA sequences of five calmodulins were found in Euglena, one of which was only known in its protein structure (CaM.1); the other four are new. The biosynthesis of the corresponding proteins of CaM.1-CaM.5 was inhibited by means of RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…7.6). This is not consistent with Daiker et al (2010), who found the presence of five calmodulins (CaM.1-5) in E. gracilis. The absence of CaM.1-7 from the genome assembly is likely due to incompleteness.…”
Section: The Tubulin and Calmodulin Genescontrasting
confidence: 68%
See 1 more Smart Citation
“…7.6). This is not consistent with Daiker et al (2010), who found the presence of five calmodulins (CaM.1-5) in E. gracilis. The absence of CaM.1-7 from the genome assembly is likely due to incompleteness.…”
Section: The Tubulin and Calmodulin Genescontrasting
confidence: 68%
“…11, this volume), oxygen pressure, gravity (gravitaxis, see Chap. 12, this volume) (Porterfield 1997;Streb et al 2002;Hader et al 2005a, b;Daiker et al 2010), and signal transduction (Daiker et al 2010). Calmodulin and protein kinases are involved in gravitaxis (Streb et al 2002).Five types of CaM proteins have been discovered in E. gracilis and include: CaM.1, CaM.2, CaM.3, CaM.4, and CaM.5, with CaM.2 being implicated in gravitaxis (Toda et al 1992;Daiker et al 2010).…”
Section: The Tubulin and Calmodulin Genesmentioning
confidence: 96%
“…These membrane proteins could allow an ion transport when activated which in some cases has been found to consist of calcium ions. At least in the case of Euglena the gated calcium activates calmodulin, 32, 113 which is a universal regulatory protein in many prokaryotic and eukaryotic taxa. 36, 114 The influx of Ca 2+ changes the membrane potential as has been found in ciliates and flagellates, which might be a subsequent step in the sensory transduction chain being responsible for signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…However, some elements of the downstream signalling cascade have recently been validated through RNA interference, such as presence of calmodulin (Daiker et al . ) and protein kinase A (Daiker et al . ).…”
Section: Introductionmentioning
confidence: 99%